DAMPAK KOMUNIKASI E-WOM TERHADAP NIAT BERKUNJUNG DENGAN CITRA DESTINASI SEBAGAI VARIABEL MEDIASI (STUDI PADA FESTIVAL TELUK JAILOLO KABUPATEN HALMAHERA BARAT) - Muhammad Agung; Ida Hidayanti; Ibnu Sina Hi. Yusuf (Jurnal Manajemen Sinergi, 2020)
Objective: The development of information and communicationtechnology that is developing rapidly can be utilized as a means tointroduce Indonesian tourism. One way that can be done is tostimulate electronic word of mouth communication betweentourists through social media Instagram, Facebook and Twitter.This study aim s to determine and analyze the effect of ElectronicWord of Mouth Communication on the Visiting Intentions mediatedby the Destination Imagery at the Jailolo Bay Festival. Thisresearch is planned to be carried out in October-December 2019.Methodology: The analytical model used are path analysis as toolsfor the statistical test. Data collection tools used are questionnairesand interviews, and the number of respondents was 95 respondent.Finding: H1, H2, H3, and H4 are accepted, at the 5% confidencelevel.Conclusion: The results of this study are that electronic word ofmouth has a positive effect on destination image and visitingintentions. This means that the more electronic word of mouthcommunication on Jailolo Bay Festival social media, the better thepopularity of the tourist destination will increase in the community.Likewise, social media users are more interested if they seeinformation and reviews presented through social accounts aboutthe state of an activity at the Jailolo Bay Festival. Furthermore, thedestination image also has a positive effect on intention. That is,the better the image of a destination at the Jailolo Bay Festival willinfluence people to visit the activity. And from Electronic word ofmouth with the intention to visit mediated by the image of destinasobtained a positive effect. This means that if the informationprovided through social media with a good opinion, in the form of apositive image of the Jailolo Bay Festival activities will increase theintention to visit tourists.